2020
DOI: 10.1016/j.landurbplan.2019.103725
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing hydropower dam location and removal in the São Francisco river basin, Brazil to balance hydropower and river biodiversity tradeoffs

Abstract: To support eco-friendly hydropower planning in developing regions, we propose a spatial optimization model for locating dams to balance tradeoffs between hydropower generation and migratory fish species richness. Our model incorporates two special features. First, it is tailored to the dispersal of tropical migratory fishes, which require long, unimpeded river stretches to complete their life-cycle. To model fish with this type of dispersal pattern, we introduce the concept of a river pathway, which represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Optimization studies of dam placement and removal often emphasize fish species richness as a societally valued attribute of ecosystems. For instance, O'Hanley et al (2020) developed a spatial optimization model for locating dams to balance trade‐offs between hydropower generation and migratory fish species richness. Their study relied on a crude ruleset describing the relationship between richness and undammed river length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization studies of dam placement and removal often emphasize fish species richness as a societally valued attribute of ecosystems. For instance, O'Hanley et al (2020) developed a spatial optimization model for locating dams to balance trade‐offs between hydropower generation and migratory fish species richness. Their study relied on a crude ruleset describing the relationship between richness and undammed river length.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial biologists have successfully leveraged SARs to explore how manipulations of fragment size, fragment quality, and matrix quality may affect biodiversity (Huth and Possingham 2011, Freeman et al 2018); whether movement corridors between fragments may slow species loss (Newmark et al 2017); and optimal configurations of protected areas. Species–area relationships in a fragmented river context could be useful for exploring potential biodiversity outcomes associated with dam additions or removals (O'Hanley et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, dams with rare fish should have regulated flow and a flood pulse component; for dams that alter the hydrological regime simulation and recovery should be completed; and for dams with potential environmental emergencies, cascade reservoir regulation should be implemented [238]. The construction site of the dam should be thoroughly investigated so that the environmental effects can be minimized, which can be achieved by spatial optimization of hydropower dam location via modeling [239].…”
Section: State-of-the-art Assessment and Evaluationmentioning
confidence: 99%
“…However, more than 50% of rivers globally are impacted by physical infrastructure (e.g., dams, weirs, and culverts) that disrupt the longitudinal connectivity and obstruct sh from accessing essential habitats and resources. Numerous studies have demonstrated the negative eect that articial barriers have on migratory (Catalano et al, 2007;Lucas et al, 2009;Gough et al, 2018;O'Hanley et al, 2020) and resident sh populations (Nislow et al, 2011), including restricted range, altered population structure, reduced spawning and recruitment success, genetic isolation, and local extinction (Woord et al, 2005;Nunn and Cowx, 2012;Barbarossa et al, 2020;Pereira et al, 2020). This, in turn, can compromise the ability of river ecosystems to deliver the full range of ecosystem services (Rounsevell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This research presented here contributes to the existing literature on systematic approaches for river connectivity enhancement. Within this literature, there exists a growing number of examples employing optimization based approaches to maximize the amount of functional habitat available for sh (Er®s et al, 2018;McManamay et al, 2019;O'Hanley et al, 2020). There are also papers that derive cost-eective solutions to optimize one or more sh population and socioeconomic metrics (King et al, 2017;Roy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%